Trends in Use of Virtual Reality (VR) Technology in Science Education: A Systematic Review - Sarpal, Simmi; Nangia, Anita (Indian Journal of Educational Technology, 2022)
The purpose of this review was to systematically identify the general trends in the use of virtual reality technology in science education. For this study, two databases ERIC and Web of science were selected for review of related articles. PICO framework was used as a review protocol. Based on inclusion-exclusion criteria 22 articles were found to be eligible for the present study. The content analysis method was employed to analyze and synthesize the data into findings. Finally, the results regarding the study objectives are graphically presented and discussed. The findings of the present review throw light into the gaps or inconsistencies in the literature as well as provide insight on the overview of the use of virtual reality in science education.